2021
DOI: 10.31098/ijrse.v3i2.604
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Teaching Competency Preparedness in Attending Field Experience Practice

Abstract: This research focuses on the readiness and the lack of students’ competence as pre-service teacher in dealing with field experience practice (PPL). The research was carried out using a mix method. Researchers develop research designs using qualitative method first, and then explain the findings obtained more comprehensively using qualitative method. The results of quantitative research were obtained through questionnaires, while qualitative data were obtained through interviews and literature studies. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Previous investigations have shown some pieces of evidence about the influence of a sense of preparedness for pre-service and in-service teachers' professional growth. However, within teacher preparation in Indonesia, not much research, particularly in the field of EFL, has examined pre-service teachers' feelings of preparedness for teaching (see Daflizar et al, 2022;Kusaeri, 2019;Loreman et al, 2013;Purwasih et al, 2021;Sari & Ridhwan, 2022). Considering the essential roles of a sense of preparedness in teacher education, there is an urgency to explore this construct further to portrait recent situations of pre-service teachers in Indonesia, which would be a potential support for the attainment of the national goals, particularly with regard to the quality of education.…”
mentioning
confidence: 99%
“…Previous investigations have shown some pieces of evidence about the influence of a sense of preparedness for pre-service and in-service teachers' professional growth. However, within teacher preparation in Indonesia, not much research, particularly in the field of EFL, has examined pre-service teachers' feelings of preparedness for teaching (see Daflizar et al, 2022;Kusaeri, 2019;Loreman et al, 2013;Purwasih et al, 2021;Sari & Ridhwan, 2022). Considering the essential roles of a sense of preparedness in teacher education, there is an urgency to explore this construct further to portrait recent situations of pre-service teachers in Indonesia, which would be a potential support for the attainment of the national goals, particularly with regard to the quality of education.…”
mentioning
confidence: 99%
“…Another common problem preservice teachers continually report is a gap in pedagogical skills. For example, a researcher examining the preparedness of 92 student teachers in Indonesia found that the students' overall preparedness for field experience practice was moderate (Purwasih, Sholichah, & Pratiwi, 2021). The present study participants reported that they were prepared better in terms of their pedagogical knowledge than their pedagogical skills and attitudes.…”
Section: Introductionmentioning
confidence: 50%
“…Teaching practice is a crucial component of teacher education programs, providing students with the opportunity to apply theory to practice and develop practical skills. Research findings suggest that teacher candidates experience significant growth and development during their student teaching experiences (Kaya & McIntyre, 2020;Naylor, Campbell-Evans & Maloney, 2015;Purwasih, Sholichah & Pratiwi, 2021). They value practical experience and hands-on learning opportunities as important components of their teacher education program.…”
Section: Introductionmentioning
confidence: 99%
“…This teaching method is carried out by actual conditions in the world of work, which will later become a profession. The vocational learning process expects students to be actively involved in solving problems, creating things, and developing HSC (Purwasih et al, 2021;Kong, 2021). However, SSC in the aviation sector is crucial in producing professional performance because aviation industry operations have high technology and risk and can guarantee flight safety.…”
Section: Introductionmentioning
confidence: 99%